Modeling and characterization of all possible triple pass EDFA configurations - Akhter, Fowzia; Ibrahimy, Muhammad Ibn; Naji, Ahmed Wathik; Siddiquei, Hasin Reza (Academic Journals, 2012)
The main purpose of designing multi-stage erbium-doped fiber amplifiers (EDFAs) is to achieve higher gain and lower noise figure for long haul optical communication. Among the multi-stage EDFAs, triple pass EDFAs were chosen in this research. This paper presents all possible triple pass EDFA configurations. The well-established one-stage mathematical models were modified to design two-stage and three-stage triple pass EDFAs. Performances of all the configurations were analyzed with pump power ratio and signal power. Optimum length and Optimum pump power ratio were also determined for each and every configuration. From the performance analysis, best triple pass EDFA was recommended for practical design.